El derecho de la competencia en el Paraguay: análisis de su aplicación en su septenio de vigencia - Andino, Cynthia (2020)
This document analyses the disenchantment and failure of the Paraguayan Competition Act, Law 4956, after seven years since it came to effect.In this article, the author studies the Competition Act, its history, as well as the Competition Authority –CONACOM–, its structure, and resolutions. Aditionally, she presents the conclusions and recommendations for its reform and future challenges.